Characteristics of a polymer Mach-Zehnder electro-optic switch using side-coupled series-cascaded M microrings - 李翠婷 郑力华 郑悦 李传南 郑传涛 (Optoelectronics letters, 2015)
Structure and design are proposed for a kind of novel polymer Mach-Zehnder electro-optic （EO） switch using side-coupled M series-cascaded EO microrings. Formulations are proposed to analyze its switching characteristics. The dependences of the device＇s performances on M are thoroughly analyzed and concluded. As the increase of M from 2 to 10, the switching voltages for the 9 devices are as low as 0.84 V, 0.82 V, 0.52 V, 0.5 V, 0.37 V, 0.36 V, 0.29 V, 0.28 V and 0.24 V, respectively; whereas the crosstalks under bar state are within -20.79-6.53 dB and those under cross state are within -20.36-5.29 dB. The analysis results indicate that a smaller M is preferred for dropping the insertion loss and crosstalk, and a larger M should be selected to increase the optical bandwidth and minimize the switching energy. Generally, due to low switching voltage, the proposed device shows potential applications in optical networks-on-chip.